2016
DOI: 10.1016/j.phrp.2015.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Community-Based Approach as Policy Tool: World Health Organization-Designated Safe Communities of Korea and Health Action Zones of the United Kingdom

Abstract: ObjectivesThe aim of this study is to ascertain and identify the effectiveness of area-based initiatives as a policy tool mediated by societal and individual factors in the five World Health Organization (WHO)-designated Safe Communities of Korea and the Health Action Zones of the United Kingdom (UK).MethodsThe Korean National Hospital discharge in-depth injury survey from the Korea Centers for Disease Control and Prevention and causes of death statistics by the Statistics Korea were used for all analyses. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Successful Safe Community programmes. There are numerous of successful working Safe Community initiatives in the various continents of the world [18][19][20][21][22][23][24][25][26][27]. A number of studies in Europe, mainly in Sweden evaluated the effect of Safe Community programs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful Safe Community programmes. There are numerous of successful working Safe Community initiatives in the various continents of the world [18][19][20][21][22][23][24][25][26][27]. A number of studies in Europe, mainly in Sweden evaluated the effect of Safe Community programs.…”
Section: Resultsmentioning
confidence: 99%
“…The study on Gangbuk-gu Safe Community showed that Safe Community program might be a helpful programme for enhancing senior safety. The qualitative outcomes, such as bringing the residents' attention to the safety, significant active participation and coordination of stakeholders, should also be considered as important factors of the communitybased initiatives [25,26]. In Iran, injury -related fatality rate significantly decreased in Kashmar Safe Community, when compared with control groups [27].…”
Section: Resultsmentioning
confidence: 99%
“…Tindana et al (2007) suggest that community engagement in research goes beyond community participation; it is a process that requires collaborative working with partners who share goals and interests. While there is some terminological blurring with the World Health Organization’s concept of community development (Kang et al , 2016), at a World Health Organization (2017) workshop aimed at developing a community engagement framework, it was defined as a ‘process of developing relationships that enable stakeholders to work together to address health-related issues and promote well-being to achieve positive health impact and outcomes’. Definitional fluidity is perhaps inevitable as there is no standard definition of community (Tindana et al , 2007).…”
Section: Definitionsmentioning
confidence: 99%
“…Definitional fluidity is perhaps inevitable as there is no standard definition of community (Tindana et al , 2007). It may commonly demarcate a geographic area (eg, a remote rural community), but could also be used to characterise a group of people living with a particular health condition or a group sharing particular value systems and cultural characteristics (George et al , 2015; Kang et al , 2016). In the South African health setting, community participation is mainly related to primary health care nurses and community health workers (currently called Ward-based Primary Health Care outreach team), who go out to the community or to the homes of community members to offer health-related information and care (Kironder and Kahirimbanyi, 2002).…”
Section: Definitionsmentioning
confidence: 99%